1989
DOI: 10.1111/j.1432-1033.1989.tb14719.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐linked oligosaccharide changes with oncogenic transformation require sialylation of multiantennae

Abstract: Glycopeptides derived from NIH 3T3 fibroblasts and these cells transformed by transfection with human DNA containin? om'i ~"~m c H-ras were analyzed by 500-MHz 'H-NMR spectroscopy and binding to immobilized lectins. The cells were mc1;iholically labeled with ~-[~H]glucosamine or ~- [~H]fucose and the glycopeptides included in Bio-Gel P-10 ( M , 5000-3500) were separated into neutral and charged fractions on DEAE-cellulose. The major portion (80%) of these [3H]fucose glycopeptides from the non-transformed NIH 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Glycans derived from gp70(NIH3T3) contained zero to four sialic acid residues, the linkage positions of which, however, were not determined due to the small amounts of material available. Data reported by Santer et al [38] on the structures of NIH3T3-derived glycopeptides as well as glycosylation analyses of the envelope glycoprotein from an ecotropic F-MuLV propagated on the same cell line (Kempf and Geyer, unpublished results) demonstrated that NIH3T3 cells contain both (a2 -6)-and (a2 -3)-sialyltransferases. Therefore, it can be assumed that the sialylated glycans obtained here are similarly substituted by (a2 -3)-and/or (a2 -6)-linked sialic acid residues.…”
Section: Discussionmentioning
confidence: 99%
“…Glycans derived from gp70(NIH3T3) contained zero to four sialic acid residues, the linkage positions of which, however, were not determined due to the small amounts of material available. Data reported by Santer et al [38] on the structures of NIH3T3-derived glycopeptides as well as glycosylation analyses of the envelope glycoprotein from an ecotropic F-MuLV propagated on the same cell line (Kempf and Geyer, unpublished results) demonstrated that NIH3T3 cells contain both (a2 -6)-and (a2 -3)-sialyltransferases. Therefore, it can be assumed that the sialylated glycans obtained here are similarly substituted by (a2 -3)-and/or (a2 -6)-linked sialic acid residues.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on freshly isolated cells or cell lines from mouse [23][24][25][26], bovine [27] and porcine origin [28] further demonstrated the presence of α-gal epitopes in large amounts on cell surface glycoconjugates. More recently, Kim et al carried out a detailed analysis of N-linked glycans from pig kidney [29].…”
Section: Glycoproteins With α-Gal Epitopesmentioning
confidence: 99%
“…An induced alteration in the glycosylation of cell surface glycoproteins that has been documented for many years concerns the significant increase in oligosaccharide size caused by oncogenic transformation using a variety of agents (6 -14). This increase in size was found to result mainly from an increase in the levels of asparagine-linked oligosaccharides containing N-acetylglucosamine linked ␤1,6 to the ␣(1,6)-linked mannose in the trimannosyl core, (GlcNAc␤(1,6)Man), and in many cases these oligosaccharides express polylactosamine that can be sialylated (15)(16)(17)(18). The (GlcNAc␤(1,6)Man) branch is synthesized by N-acetylglucosaminyltransferase V (GlcNAc-T V), 1 the enzyme whose activity is significantly and selectively increased after transformation by tumor viruses or isolated oncogenes (16, 19 -22).…”
mentioning
confidence: 99%